1995
DOI: 10.1021/ja00140a028
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Deprotonation as a Vehicle for the Asymmetric Synthesis of C2-Symmetric P-Chiral Diphosphines

Abstract: Chiral diphosphines1 are the ligands of choice for a wide range of enantioselective transition-metal-catalyzed processes.2 While chirality may be independently incorporated on either

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
179
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 276 publications
(186 citation statements)
references
References 1 publication
6
179
0
1
Order By: Relevance
“…The method has also been applied to N-Bocpyrrolidines, [10,11] several benzylic substrates, [12] ferrocenes, [13] P,P-dimethylarylphosphane derivatives, [14] as well as to the kinetic resolution of a racemic allyl carbamate [15] and of several b-stereogenic alkyl carbamates. [16] Moreover, a desymmetrization of meso-oxabicycles by alkyllithium/(À)-sparteine-induced ring-opening has been described by Lautens et al [17] and Hodgson et al [18] The (À)-sparteine-induced deprotonation of alkyl carbamates 3 generated from primary alcohols, which bear nonmesomerically stabilizing groups adjacent to the carbanionic center in 5, is characterized by a pronounced pro-S selectivity in the deprotonation step.…”
Section: Introductionmentioning
confidence: 99%
“…The method has also been applied to N-Bocpyrrolidines, [10,11] several benzylic substrates, [12] ferrocenes, [13] P,P-dimethylarylphosphane derivatives, [14] as well as to the kinetic resolution of a racemic allyl carbamate [15] and of several b-stereogenic alkyl carbamates. [16] Moreover, a desymmetrization of meso-oxabicycles by alkyllithium/(À)-sparteine-induced ring-opening has been described by Lautens et al [17] and Hodgson et al [18] The (À)-sparteine-induced deprotonation of alkyl carbamates 3 generated from primary alcohols, which bear nonmesomerically stabilizing groups adjacent to the carbanionic center in 5, is characterized by a pronounced pro-S selectivity in the deprotonation step.…”
Section: Introductionmentioning
confidence: 99%
“…The yields were satisfactory-to-high in all experiments and the products obtained were generally white crystalline solids. Although we have analysed the products as the phosphaneϪborane complexes, decomplexation to the free phosphane can be effected using amines [4,18] or treatment with acid followed by hydrolysis. [6,19] …”
Section: Resultsmentioning
confidence: 99%
“…[3] An elegant approach involving the enantioselective deprotonation of prochiral dimethylphosphaneϪboranes with a (Ϫ)-sparteine·butyllithium complex has been developed by Evans, [4] while Livinghouse has reported a related study concerning the dynamic resolution of lithiated racemic tert-butylphenylphosphaneϪborane. [5] Imamoto has applied the enantioselective deprotonation approach both to the preparation of the BisP* [6] and MiniPHOS [7] ligands, while Zhang et al have again shown the elegance of the (Ϫ)-sparteine·butyllithium method in their synthesis of Tangphos.…”
Section: Introductionmentioning
confidence: 99%
“…Trichlorophosphine was converted into alkyldimethylphosphine-boranes (12) in one pot, and these, in turn, were subjected to enantioselective deprotonation with s-BuLi/(-)-sparteine in ether. 13 The resulting enantiomerically enriched organolithium compounds (13) were oxidatively dimerized on treatment with CuCl2 to give compounds 14 in good yields. Subsequent removal of the boranato groups by the reaction with amine was unsuccessful, but it was accomplished by using the method developed by McKinstry and Livinghouse.…”
Section: Optically Pure 12-bis [(O-alkylphenyl)phenylphosphino] -Ethmentioning
confidence: 99%